ASPEK HUKUM INTERNASIONAL DALAM ADVOKASI AMNESTY INTERNATIONAL TERHADAP PERMASALAHAN MAIL ORDER BRIDES DARI NEGARA TIONGKOK - An Nisaa Mujahidina; Zulfikar Jayakusuma; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
At the world level human trafficking is a transnational criminal act and is declareda violation of human rights. So the trafficking of people is an act contrary to humandignity and violates human rights. Mail order bride as a new modus operandi andbecome part of human trafficking. Making Amnesty International a non-governmentalinstitution develops and conducts research with a globally connected writing networkand can conduct a wide range of campaign tactics, protests, and various othertransnational activities. In this case it carried out a strategy in an effort to develop newinternational legal norms on humanitarian issues related to this case.This type of research can be classified as a type of normativeresearch, In legalresearch the type of law is conceptualized as what is written in thelegislation (Law InThe Books) or the law is conceptualized as a rule of law which is the benchmarks ofbehaving or behaving appropriately or inappropriately by utilizing descriptive methods.This research is normative juridical research on legal systematics. Research into legalsystematics is conducted against a particular legislation or written law. The purpose isto conduct an identify against the basic or basic understanding of rights andobligations, legal events, legal relationships,From the results of research and discussion can be concluded that, AmnestyInternational provides a stronger guarantee of enforcing human rights. AmnestyInternational operates on the principles of international security, global security,human rights universality, impartiality, self-reliance, democracy and mutual respect.The organization also respects the law and applies human rights standardsinternationally. With the spread of a non-governmental such as amnesty international increating a good cooperation in order to run continuously, then there is a driving factor– a driver that serves as a reinforcement of cooperation in tackling the problem of brideorders.Keywords :Human Trafficking, Bride Or